Taxonomic review of the Miltochrista pudibunda (Snellen) species-group (Lepidoptera: Erebidae: Arctiinae) with description of a new species - Volynkin, Anton V.; Singh, Navneet; Černý, Karel; Joshi, Rahul (Zootaxa, 2021)
The Miltochrista pudibunda (Snellen, 1880) species-group is reviewed. A new synonym is established: M. pudibunda = M. irregularis Rothschild, 1913, syn. nov. The species previously treated by authors (since Hampson (1900)) as M. pudibunda is described as new: M. berdepsebunda sp. nov. A lectotype female is designated for Miltochrista irregularis Rothschild, 1913. Adults together with male and female genitalia of all species of the group are illustrated, diagnoses are provided for each species.